Political regimes and economic development in Ghana’s Fourth Republic - Ayisi-Boateng, George (My University, 2021)
This study contributes to the state of knowledge on the role of political regimes in the development of Ghana from 1993-2020. It positions the discourse in terms of how political regimes facilitate, and/or inhibit the economic development process since the dawn of the Fourth Republic. Drawing on the critical realist research framework, the study examines the impact of the two dominant political parties that have held power since 1992: the New Patriotic Party (NPP) and the National Democratic Congress (NDC). It specifically examines the nature of economic policies, their implementation and out turns. The findings indicate that the two political parties tend to devote much of their attention to addressing the negative propaganda narratives from opposing camps. This type of “communication war” finds expression in the manifestos and development plans, and has been the bane of Ghana’s development trajectory over the past three decades. The study argues that, although significant amount of sound policies have been written on paper, implementation challenges have been the Achilles’ heels of both regimes. Within the global context, Ghana’s multi-party democracy has been applauded and, whilst some of the development agenda have been home-grown, the political regimes have borrowed policies from other developed economies. In the economic sphere, we identify a plethora of policy slippages in relation to job creation and entrepreneurial development, ranging from lack of political will, to putting square pegs in round holes, and widespread mismanagement. Among other things, the study highlights how the political parties could begin to find ways of working together in the area of development plan formulation and implementation. The idea is that the consultative / participatory approach to addressing the development problems of the country has the potential to put an end to the current fragmented, short term and unpredictable nature of the “national” development plans. It is hoped this study will provide utility for further academic and policy research and help answer important questions surrounding the current and future state of business development in Ghana and countries of similar circumstances
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy in Political Economy to the Faculty of Commerce, Law and Management, The Graduate School of Business Administration, University of the Witwatersrand, Johannesburg, 2021
Keywords: Critical realist theory; Political regimes; Ghana’s business sector; UCTD; SDG-8: Decent work and economic growth